Fecal microbiome and functional prediction profiles of horses with and without crib-biting behavior: A comparative study (2024)
ABSTRACT: Crib-biting is a stereotyped oral behavior with poorly understood etiology and pathophysiology. The relationship between the gut microbiome and brain function has been described in behavioral disorders such as schizophrenia, depression and anxiety in humans. In horses, studies of behavioral problems and the microbiome are very limited. This study aimed to characterize the fecal microbiome and the predicted functional profile of horses with and without aerophagia. Fecal samples were collected from 12 Colombian Creole Horses of both sexes, divided into two groups: group 1, composed of six horses with crib-biting (3 females and 3 males), average body weight of 330 ± 10 kg, age of 7.0 ± 1.2 years and body condition score (BCS) of 5/9 ± 1 and group 2, consisting of six horses without crib-biting (3 females and 3 males), average body weight of 335 ± 5 kg, age 6.5 ± 1 years and BCS of 6/9 ± 1. From each horse in both groups fecal total DNA was obtained and 16S ribosomal RNA gene amplicons were sequenced to characterize the bacterial community structure. Community structure and differential abundance analyses revealed significant differences between the two conditions (p < 0.05). Specifically, the fecal microbiota at the family level in crib-biting horses, showing a decrease in Bacteroidales and an increase in Bacillota and Clostridia, differed from that of healthy horses without crib-biting, consistent with findings from previous studies. Furthermore, metagenome prediction suggests metabolic profile changes in bacterial communities between both conditions in horses. Further studies are required to validate the role of the microbiota-gut-brain axis in the etiology of crib-biting and other abnormal and stereotyped behaviors.